2008
DOI: 10.1002/lapl.200810068
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-three-level Nd:GdVO4laser under diode pumping directly into the emitting level

Abstract: Abstract:We present experimental investigation on quasi-threelevel operation of Nd:GdVO4 laser under 879 nm laser diode pumping into the emitting level. By using a 5-mm-long, 0.2-at.% bulk crystal, the maximal 3.65 W continuous wave 912 nm laser is obtained under 16.5 W pump power. The slope efficiency is 35.9% and the optical conversion efficiency is 22.1% with respect to the absorbed pump power. The beam quality factor is about 1.83 for 3.0 W output power at 912 nm. The good results demonstrate that the 879 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In order to solve this problem, one promising technique which fulfill these requirements is select a pump source at 888 nm or 879 nm directly to the upper emission level [23,24], another technique is use double end pump configuration [25] and at the same time lower the doping concentration of the laser crystal to enhance the homogeneous pump light distribution to avoided the fracture and scaling the output power at higher pump power [26].…”
Section: +mentioning
confidence: 99%
“…In order to solve this problem, one promising technique which fulfill these requirements is select a pump source at 888 nm or 879 nm directly to the upper emission level [23,24], another technique is use double end pump configuration [25] and at the same time lower the doping concentration of the laser crystal to enhance the homogeneous pump light distribution to avoided the fracture and scaling the output power at higher pump power [26].…”
Section: +mentioning
confidence: 99%
“…Successful attempts to lase the Nd:LuVO 4 have been reported [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Recently, the Nd:LuVO 4 laser under direct 880 nm diode laser pumping was reported [53][54][55][56][57][58]. In 2010, Lü et al reported diode pumped Nd:LuVO 4 laser emitting at 1089 nm for the first time.…”
Section: Introductionmentioning
confidence: 97%
“…A more efficient pumping method was presented and researched [44][45][46][47][48], which was to pump the Nd 3+ ions directly into the 4 F 3/2 upper lasing level.…”
Section: Introductionmentioning
confidence: 99%